THE ROLE OF DIGITALIZATION IN MODERN EDUCATION - Khayrieva Madina Ilhomovna; Mamayusupov Akobir Normumin ogli (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2026)
This article examines the growing influence of digitalization in modern education. It discusses how digital tools, online platforms, and emerging technologies have transformed traditional teaching and learning environments. The study outlines key advantages such as improved access to resources, personalized learning, greater engagement, and administrative efficiency, while also addressing challenges including the digital divide, cybersecurity concerns, and teacher readiness. The article concludes that digitalization has become an essential component of 21st-century education and will continue shaping the future of learning.